Clinical Management of Preeclampsia - Huertas, Erasmo (2015)
The most important issue in preeclampsia management is an adequate prenatal care in order to identify high risk women as well as early recognition of clinical signs and symptoms and progression to severe stages. The main objective in treatment is maternal safety. Decision to end gestation or expectant management will depend on gestational age, fetal and maternal condition, labor or no labor and membranes status.